Stability analysis and vibration control of a class of negative imaginary systems - Abdullahi, A. M.; Mohamed, Z; Zainal Abidin, S; Akmeliawati, Rini; Bature, Amiru A. (Universiti Teknologi Malaysia, 2015)
This paper presents stability analysis and vibration control of a class of negative imaginary systems. A flexible manipulator that moves in a horizontal plane is considered and is modelled using the finite element method. The system with two poles at the origin is shown to possess negative imaginary properties. Subsequently, an integral resonant controller (IRC) which is a strictly negative imaginary controller is designed for the position and vibration control of the system. Using the IRC, the closed-loop system is observed to be internally stable and simuation results show that satisfactory hub angle response is achieved. Furthermore, vibration magnitudes at the resonance modes are suppressed by 48 dB.